Population et sociétés - Institut national d'études démographiques (France) (Paris : Institut national d'études démographiques, 1968)
"Bulletin mensuel d'informations démographiques, économiques, sociales."
Latest issue consulted: No 473 (déc. 2010).
Keywords: Demography -- Periodicals; Population -- Periodicals; Population -- Périodiques.; Demography; Population; POPULATION; POPULATION DYNAMICS; DEMOGRAPHY; SOCIAL ASPECTS; Population; Electronic journals